VENN DIAGRAM METHOD FOR STUDENTS’ ABILITY IN WRITING AT INTENSIVE ENGLISH CLASS OF UNISMUH MAKASSAR (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2012)
The objectives of this research are to find out the improvement of the students’ writing ability in terms of content and organization through Venn Diagram Method at Class A students of Intensive English Class. This research used Classroom Action Research (CAR). It had conducted two cycles. Where each cycle has consisted of four meeting. It employed writing test as the instrument. The number subject of the research was 28 students and consist of 5 men and 23 women. Implementation of the first and the second cycle during the four meeting. The technique of the data collection used the cycle, based on the material being taught. Based on the findings of the research, the improvement of the students’ writing ability in content and organization were significantly improved. Where the mean score in content was 7.79 and mean score in the organization was 7.57. It’s mean that by using Venn Diagram method can improve the students’ writing ability.Keywords: Venn Diagram, Method, Writing.